H∞ current damping control of DFIG based wind farm for sub-synchronous control interaction mitigation. (June 2018) - Wang, Yun; Wu, Qiuwei; Yang, Rong; Tao, Guoqing; Liu, Zhaoxi
Highlights: An H∞ damping controller is developed for the DFIG based WF to mitigate SSI. The robust stability (RS) and robust performance (RP) of the system are validated by the µ analysis. The performance of the H∞ damping controller is demonstrated by time domain simulations. The worst case scenario shows the superior performance of the H∞ damping controller. Abstract: This paper proposes an H∞ damping controller for the doubly-fed induction generator (DFIG) based wind farm (WF) to mitigate sub-synchronous control interactions (SSCI) with series capacitor compensated lines. A multi-input multi-output (MIMO) uncertain state-space model is developed to reflect the main SSCI characteristics considering the uncertainties of wind speed, series compensation (SC) levels and system parameters. The SSCI is analyzed using the eigenvalue analysis of the uncertain system model. In order to damp the SSCI between the WF and series capacitor compensated lines under uncertainties, an H∞ damping controller is designed for the rotor side converter (RSC). The weighting functions are designed to meet the mitigation requirements of sub-synchronous oscillation currents and output power. The robust stability (RS) and robust performance (RP) of the system are validated by the µ analysis. The performance of the H∞ damping controller is demonstrated by time domain simulations of a 90 MW wind farm model with different wind speed, and SC levels. The case study with 6 m/s wind speed and 70% SC level shows superior performance of the H∞ damping controller.